2020
DOI: 10.1103/physrevlett.125.214501
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Ekman Plumes and Vortex Condensates in Rapidly Rotating Thermal Convection

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…However, studies comparing no-slip and stress-free conditions could not see LSVs for no-slip plates at the same parameters where the stress-free case did display LSV formation [78,79], or only transiently would LSVs grow to be destroyed again shortly after [66]. By using higher Ra/Ra C values than before at small E, Aguirre Guzmán et al [80] have found stable LSVs in domains with no-slip plates at Pr = 5.2, E = 10 −7 , Ra/Ra C > 40, and at Pr = 0.1, 2 × 10 −7 ≤ E ≤ 5 × 10 −7 , Ra = 10 10 . Indeed, stronger buoyant forcing is required for the upscale energy transfer to withstand the Ekman-plume perturbations to the bulk from the no-slip boundaries and achieve LSV formation.…”
Section: Convection In Periodic Domainsmentioning
confidence: 93%
See 4 more Smart Citations
“…However, studies comparing no-slip and stress-free conditions could not see LSVs for no-slip plates at the same parameters where the stress-free case did display LSV formation [78,79], or only transiently would LSVs grow to be destroyed again shortly after [66]. By using higher Ra/Ra C values than before at small E, Aguirre Guzmán et al [80] have found stable LSVs in domains with no-slip plates at Pr = 5.2, E = 10 −7 , Ra/Ra C > 40, and at Pr = 0.1, 2 × 10 −7 ≤ E ≤ 5 × 10 −7 , Ra = 10 10 . Indeed, stronger buoyant forcing is required for the upscale energy transfer to withstand the Ekman-plume perturbations to the bulk from the no-slip boundaries and achieve LSV formation.…”
Section: Convection In Periodic Domainsmentioning
confidence: 93%
“…I thus introduce a 'rotation-affected' range 2a, and a 'rotation-dominated' range 2b. In range 2b, the flow state of geostrophic turbulence remains mostly out of reach at large Pr: asymptotic simulations at Pr = 3 have reported it; a recent DNS study [80] has observed LSVs at Pr = 5.2, where their generation mechanism of upscale energy transfer is a characteristic feature of geostrophic turbulence. It is not clear where to place the upper boundary of the geostrophic regime, that in fact encompasses all four flow types (cells, columns, plumes and geostrophic turbulence) and is indicated with the shaded area in Figure 2(b).…”
Section: A Sketch Of the Geostrophic Regimementioning
confidence: 97%
See 3 more Smart Citations